"I Won't Back Down?" Complexity and Courage in Government Executive Decision Making. (12th November 2015) - Kelman, Steven; Sanders, Ronald; Pandit, Gayatri
Abstract: Senior government executives make many difficult decisions, but research suggests that individual cognitive limitations and the pathologies of "groupthink" impede their ability to make value‐maximizing choices. From this literature has emerged a normative model that Irving Janis calls "vigilant problem solving, " a process intended for the most complex decisions. To explore its use by senior public officials, the authors interviewed 20 heads of subcabinet‐level organizations in the U.S. federal government, asking how they made their most difficult decisions. The initial focus was on whether they employed a vigilant approach to making decisions that were informationally, technically, or politically complex. Most executives identified their single most‐difficult decision as one that required courage; they often made such courageous decisions after personal reflection and/or consultation with a small number of trusted advisors rather in ways that could be described as vigilant. The different approaches for making complex decisions, compared with those involving courage, are discussed and a contingency model of effective executive decision making is proposed that requires leaders (and their advisors) to be "ambidextrous" in their approach .